Rostovtzeﬀ and his Social and Economic History of the Roman Empire: A Comment on a Scholarly Masterpiece - Panchenko, Dmitri (Hyperboreus, 2021)
The reputation of The Social and Economic History of the Roman Empire (1926) is contradictory. On the one hand, Rostovtzeﬀ’s work has been recognized as a masterpiece. On the other hand, its main ideas have been repeatedly dismissed. The critics pointed to the personal experience of Rostovtzeﬀ, an exile from revolutionary Russia; they saw in his argument the intrusion of the concerns that properly pertain to Russian history. However, there is no direct retrojection of Russian conditions onto the Roman Empire in Rostovtzeﬀ’s work, and his personal experience, that of a historian emotionally preoccupied with the problems of his own time, gave him a more acute vision of comparable phenomena of the past. The ideas of The Social and Economic History of the Roman Empire  are in fact profound and persuasive though, of course, not all of them are unimpeachable. The book traces the fate of the Roman Empire with its institutions, social groups and economy. It is a tragic story of “how and why the brilliant life of the early Empire so completely degenerated into the primitive and half-barbarous life of the later period”, and here the reader senses the emotional nvolvement of the author. Such and similar features of The Social and Economic History of the Roman Empire make this book, with its formidable scholarly apparatus, akin to all great books that illuminate the human condition, and to the grand European novels in particular, and this must be recognized as a remarkable achievement rather than an idiosyncrasy.